Addressing cytotoxicity of 1, 4-biphenyl amide derivatives: Discovery of new potent and selective 17β-hydroxysteroid dehydrogenase type 2 inhibitors. Issue 1 (1st January 2016) - Gargano, Emanuele Marco; Perspicace, Enrico; Carotti, Angelo; Marchais-Oberwinkler, Sandrine; Hartmann, Rolf W.
Graphical abstract: Abstract: Four different classes of new 17β-hydroxysteroid dehydrogenase type 2 (17β-HSD2) inhibitors were synthesized, in order to lower the cytotoxicity exhibited by the lead compoundA, via disrupting the linearity and the aromaticity of the biphenyl moiety. Compounds3, 4, 7a and8 displayed comparable or better inhibitory activity and selectivity, as well as a lower cytotoxic effect, compared to the reference compoundA . The best compound4 (IC50  = 160 nM, selectivity factor = 168, LD50  ≈ 25 μM) turned out as new lead compound for inhibition of 17β-HSD2.